MODELLING OF LOCAL SCOUR IN ENERGY DISSIPATION SYSTEM - RASOOL, AYESHA GHULAM (2013)
The scour process downstream of hydraulic structures is one of the primary factors that must be identified and controlled to avoid the structural collapse or material failure. This research presents prediction models for the local scours that occur due to medium and high discharges from an outflow structure near stilling basin. This research employs statistical approach in order to predict local scour as majority ofthe prediction models are based on deterministic equations.